If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12y + 3x = 7 Reorder the terms: 3x + 12y = 7 Solving 3x + 12y = 7 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-12y' to each side of the equation. 3x + 12y + -12y = 7 + -12y Combine like terms: 12y + -12y = 0 3x + 0 = 7 + -12y 3x = 7 + -12y Divide each side by '3'. x = 2.333333333 + -4y Simplifying x = 2.333333333 + -4y
| 2x^3-5x^2-2x+15=0 | | 11y-4y=28 | | 5n+4n=36 | | 0.50x+0.15(50)=47.5 | | 24w+45=-3w^2 | | 5x(2x+1)+2x+1=0 | | 7d-5d=4 | | 4v^3-3v^2-20v+15= | | 2a+3-9a=3a | | 0=4x^2+31x+46 | | -4y+6=-2(3y+2) | | (x+21)=(2x-14) | | 2(4n+9)=-6+8(3-12n) | | 25u^6v^6y-10u^7v^7= | | 16Y-8(3y-2)=24 | | 6x-9=12+3x | | 5(r-7)=8(r+2) | | 2(4x+4)=10x+6-2x+2 | | 3n-17=3+5n | | 4-5w=-2w | | -7Y+4=60 | | 25x=625 | | -3+4(1-3m)=-12(m-11) | | 16m^2-8m-3= | | y=3x^2+12x+7 | | X+10Y=47 | | ln(2x+3)=ln(2x-1) | | -7(v-5)=-7(v+8) | | 16=16H | | 2x^2-8x-80=0 | | 8t-18=38+t | | X+6+6x=41 |